Extra-axial ependymoma mimicking a meningioma - Sai Sudarsan Puduru; B.J. Rajesh; Milap Shah (Indian Journal of Neurosurgery)
Supratentorial ependymomas are rare and are usually intra axial in location. We report a case of extra axial supra tentorial ependymoma in a girl which mimicked a falcine meningioma. Imaging, pathological features and management are described in this case report along with review of the literature. The possible origin of these tumors is discussed.